Pressure Effect on Turbidity, pH, Lead Content, and Coliform during the Demineralization Process of Brackish Water - Camelia Amandasari; Ilma Fadlilah; Rosita Dwityaningsih (CHEESA: Chemical Engineering Research Articles, 2025)
Brackish water is a mixture of freshwater and seawater and typically exhibits intermediate physicochemical characteristics. Cilacap City is located in a coastal area, resulting in the mixing of freshwater from river systems with seawater intrusion, thereby producing brackish water with relatively high mineral content. Demineralization is a water purification method that can be applied to treat this type of water or wastewater, producing water with significantly reduced mineral content suitable for various uses. Therefore, this research aimed to investigate the effects of operating pressure on turbidity, pH levels, lead (Pb) concentration, and coliform content during the demineralization of brackish water. This research was carried out from March to June, and the sample of brackish water was obtained from the Northern Cilacap Payau Forest Tour Area. Purification method of demineralization process consists of the filtering of silica sand, zeolite adsorption, membrane filtration, and ion exchange with anion resin and cation resin repeatedly. The best result obtained was a pressure of 10 psi with a pH level of 5.9, decreasing turbidity of 90.81%, lead level content of 28.125%, and coliform bacteria of 55.49%